Keanekaragaman dan Status Konservasi Burung Air di Kawasan Danau Perintis Kabupaten Bone Bolango Gorontalo - Wafika Tasya; Mustamin Ibrahim; Zuliyanto Zakaria (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Perintis lake is a significant aquatic area with considerable potential as a habitat for various bird species, as it is surrounded by forest and agricultural areas that support a diverse avifauna. This research aimed to determine the diversity and conservation status of waterbird species in the perintis lake area. The research employed survery method by determining observations stations and following the water flow river transect along the lake using a boat while recording all birds seen or heard. The results identified several waterbird species, including the Collared Kingfisher (Todiramphus chloris), Purple Heron (Ardea purpurea), Black-crowned Night Heron (Nycticorax nycticorax), Cerulean Kingfisher (Alcedo coerulescens), White-browed Crake (Porzana cinerea), Javan Pond Heron (Butorides striata javanica), Barred Rail (Gallirallus torquatus) and Javan Pond Heron (Ardeola speciosa). The conclusions are as follows : (1) The waterbird diversity index (H’) at perintis lake ranged from 1.365 to 1.912, which falls into the moderate category, indicating that the waterbird community in thus lake is fairly diverse; (2) The evennes index (E) ranged from 0.378 to 0.526, indicating that the distribution of individuals among species is relatively stable